Improving flushing processes through targeted control of the temperature boundary conditions - Liebmann, Vera; Heide, Matti; Köhler, Hannes; Rüdiger, Frank; Fröhlich, Jochen (Proceedings in applied mathematics and mechanics, 2023)
In this contribution the authors investigate how flushing of chocolate using a follow‐up chocolate in a straight horizontal pipe is affected by temperature. The authors investigate a non‐uniform distribution of temperature across the considered domain. This is done using two cases, where the first exhibits a wall temperature deviating from the normal process temperature and the second exhibits a differently tempered follow‐up chocolate. The investigations are performed using unsteady three‐dimensional numerical simulations with an OpenFOAM multiphase solver, which is extended to include an additional equation for energy conservation. The physical properties of the chocolate are analyzed with respect to their dependence on temperature and implemented in a new model in OpenFOAM. The results of both cases are assessed according to industrially relevant questions. Among others, they include the amount of follow‐up chocolate needed to achieve a set goal of cleanliness. The time needed to achieve this is also considered. A dimensionless time is used to compare the different cases. Recommendations are provided on how different temperature of pipe wall and follow‐up chocolate may lead to improved flushing processes and which savings may be achieved with this strategy.